Consuming Habits Fast Food and the incidence of obesity in elementary school students - Baithesda; Juliastri Anggraini Schu; Autry Alvian Mandagi (JOURNAL of HEALTH SCIENCE REVIEW, 2024)
Obesity has become a global pandemic throughout the world and is declared the largest chronic health problem, making it a major public health problem, including for school-aged children. The aim of this research is to identify the relationship between consumption fast food and the incidence of obesity in elementary school students. Design approach cross-sectional with a student population in one of the elementary schools in Manado City. The number of respondents was 162 people with the criteria being aged 6 years and over and having consent from their parents, taken using techniques quota sampling. Fast food consumption data was collected using a paper-based questionnaire, while the incidence of obesity was measured by BMI. Data were analyzed using the Chi-square test with significance values p ≤ 0.005. The research results showed a significant relationship between consumption frequency fast food with the incidence of obesity in students (p < 0.001). It is recommended for schools to provide school canteens that comply with health standards and for parents to prepare a healthy breakfast for children.